1984
DOI: 10.1023/a:1016322524471
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two new lipophilic terbutaline ester prodrugs - the biscarbamate bambuterol (pINN) and the cascade ester D 2438 - have been designed with the goal to achieve enhanced absorption and high hydrolytic stability during first-pass in order to prolong the effect duration of the parent compound. Bambuterol, the bis-N,N-dimethyl-carbamate of terbutaline, displays improved hydrolytic stability, partly by inhibition of its own hydrolysis, and has been shown to survive first-pass hydrolysis in the dog to a high degree. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Its presence in high amounts in serum suggest a clinical role in the degradation of a variety of drugs, including succinylcholine, heroin, cocaine, and physostigmine'g-21 and in the activation of others, such as of bambuterol. 22 Finally, BChE has been suggested to act as a protective enzymatic system to guard AChE against inhibition by false substrates, preserving the critical function of AChE in its regulation of cardiovascular, neuromuscular and central cholinergic activities. In summary, these enzymes are found in a variety of molecular forms throughout the body (as outlined in Fig. 2) at both extracellular and intracellular sites, and possess an array of physiological roles, the most important of which involve regulation of cholinergic neurotransmission (as outlined in Fig.…”
Section: 17)mentioning
confidence: 99%
“…Its presence in high amounts in serum suggest a clinical role in the degradation of a variety of drugs, including succinylcholine, heroin, cocaine, and physostigmine'g-21 and in the activation of others, such as of bambuterol. 22 Finally, BChE has been suggested to act as a protective enzymatic system to guard AChE against inhibition by false substrates, preserving the critical function of AChE in its regulation of cardiovascular, neuromuscular and central cholinergic activities. In summary, these enzymes are found in a variety of molecular forms throughout the body (as outlined in Fig. 2) at both extracellular and intracellular sites, and possess an array of physiological roles, the most important of which involve regulation of cholinergic neurotransmission (as outlined in Fig.…”
Section: 17)mentioning
confidence: 99%
“…Conventional cholesterol-lowering treatments such as statin are only modestly effective. Bambuterol is a type of β2-agonist commonly used for the treatment of asthma and COPD with the advantage of once daily dosing and favorable side effect profile ( Olsson and Svensson, 1984 , D'Alonzo et al, 1995 , Sitar et al, 1993 ). In this open-label, randomized phase I clinical trial, we showed that R-bambuterol significantly lower the plasma levels of LDL-C, and marginally raise the ratio of ApoA1/ApoB, an indicator of HDL-C/LDL-C, in less than 2 h after administration and in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Bambuterol is a prodrug of the β2-agonist terbutaline. It is commonly prescribed for asthma and chronic obstructive pulmonary disease (COPD) with once daily dosing and documented clinical safety ( Olsson and Svensson, 1984 , D'Alonzo et al, 1995 , Sitar et al, 1993 ). It has been reported previously that bambuterol increases the level of high-density lipoprotein cholesterol (HDL-C) in patients with hyperlipidemia ( FlorÉN et al, 1997 ) and in patients with type II diabetes mellitus ( Bitzén et al, 1993 ) after six to eight weeks of treatments.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the prolonged lifetime exhibited by prodrugs which contain this moiety. [60,61] The hydrolysis of propionic acid ester 4 was then followed by HPLC analysis (Figure 3). Upon the addition of plasma, compound 4 was rapidly converted into a number of well resolved intermediate adducts, presumably containing one or more prodrug moieties (Figure 3C).…”
Section: Compoundmentioning
confidence: 99%